THE EFFECTIVENESS OF THE CIRCUIT LEARNING MODEL ASSISTED BY QUARTET CARDS ON SOCIAL STUDIES LEARNING OUTCOMES - Nora Sara Damayanti; Muhammad Imaduddin (STKIP Subang, 2024)
Based on pre-research data from fourth-grade students at SDN Gugus Sultan Agung, Jepara, the Social Studies learning outcomes were found to be suboptimal. The learning model used tended to be teacher-centered, with image-based learning media. This research is an experimental study using cluster random sampling, with a population consisting of 158 fourth-grade students from SDN Gugus Sultan Agung, Jepara. The sample used was SD Negeri 02 Pecangaan Wetan as the control group and SD Negeri 01 Karangrandu as the experimental group. The aim of this study is to describe the learning outcomes of fourth-grade students at SDN Gugus Sultan and to test the effectiveness of the Circuit Learning model assisted by quartet cards on Social Studies learning outcomes. The results show that the experimental group scored higher, at 76.3, compared to the control group, which only scored 66.6. The hypothesis test results indicate that tcalculated = 2.9627 > ttable = 2.0009, meaning the null hypothesis is rejected, which shows that the Circuit Learning model assisted by quartet cards is effective for teaching Social Studies to fourth-grade students. The conclusion of this research is that the Circuit Learning model assisted by quartet cards is more effective for teaching Social Studies on the topic of Hindu-Buddhist historical heritage compared to the Direct Instruction model for fourth-grade students at SDN Gugus Sultan Agung, Jepara. Keywords: circuit learning, social studies, quartet card